A cell polarity protein aPKCλ is required for eye lens formation and growth - Sugiyama, Yuki (Elsevier, 2009)
The organisation of individual cells into a functional three-dimensional tissue is still a major question in developmental biology. Modulation of epithelial cell shape is a critical driving force in forming tissues. This is well illustrated in the eye lens where epithelial cells elongate extensively during their differentiation into fibre cells. It is at the lens equator that epithelial cells elongate along their apical–basal axis. During this process the elongating epithelial cells and their earliest fibre cell derivatives remain anchored at their apical tips, forming a discrete region or modiolus, which we term the lens fulcrum. How this is achieved has received scant attention and is little understood. Here, we show that conditional depletion of aPKCλ, a central effector of the PAR polarity complex, disrupts the apical junctions in elongating epithelial cells so that the lens fulcrum fails to form. This results in disorganised fibre cell alignment that then causes cataract. Interestingly, aPKCλ depletion also promotes epithelial–mesenchymal transition of the lens epithelial cells, reducing their proliferation, leading ultimately to a small lens and microphthalmia. These observations indicate that aPKCλ, a regulator of polarity and apical junctions, is required for development of a lens that is the correct size and shape.